Characterization of tropical cyclone rapid intensification under two types of El Niño events in the Western North Pacific. (31st October 2019) - Shi, Donglei; Ge, Xuyang; Peng, Melinda; Li, Tim
Abstract: This study investigates the impacts of two different El Niño scenarios, the east Pacific warming El Niño (EPW) and the central Pacific warming El Niño (CPW), on the tropical cyclone (TC) rapid intensification (RI) in the western North Pacific (WNP). The ratio of TCs with at least one RI occurrence (RITC) to all TC numbers (RITC ratio) shows different monthly variations between the two El Niño groups. Higher RITC ratio is found during July–October (November–December) for the EPW (CPW) years. Further analyses indicate that the difference in the RITC ratio is attributed to differences in TC genesis locations, TC tracks and large‐scale environmental conditions. During July–October (TC peak season), TCs formed more in the southeastern region with EPW than with CPW. TCs in the southeastern WNP tend to move westward (northward) in the presence of weak (significant southerly) steering flow anomalies in EPW (CPW), allowing a longer (shorter) duration over the warm tropical ocean. Meanwhile, a smaller environmental vertical wind shear is also observed in the main RI region with EPW. These two mechanisms contribute to a higher peak‐season RITC ratio in the EPW years. During November–December (late season) of the EPW years, the southern WNP is dominated by anomalous anticyclonic flow that suppresses TC genesis and intensification, which leads to notably less TC frequency and RITC ratio. The anomalous equatorial heating source near the dateline induces cyclonic flow in the southeastern WNP through Gill‐type response during the late season in CPW years. The resulting larger low‐level relative vorticity, stronger upward motion, higher mid‐level relative humidity and weaker vertical wind shear all favour TCs genesis over the southeastern WNP and their subsequent intensification in the main RI region . In addition, a greater TC heat potential is evident during the late season in CPW. Hence, the more favourable atmospheric and oceanic conditions result in a greater late‐season RITC ratio in CPW than in EPW. Abstract : Composites of the SST anomalies (K) during July–November for (a) EPW, (b) CPW.